ANALISIS KERUSAKAN JALAN BERDASARKAN METODE BINA MARGA DAN DAMPAKNYA TERHADAP PENGGUNA (STUDI KASUS : JALAN NASIONAL LINTAS TIMUR SIMPANG PANGAT STA.0+000 S.D STA.3+000) - Alfian Saleh; Dedek Syariah; Fadrizal Lubis (FROPIL (Forum Profesional Teknik Sipil), 2022)
The East Cross National Road Simpang Pangat is a road network for the distribution of goods and services (international activities). This study was conducted with the aim of knowing the types of damage that occurred by observing the condition of the pavement directly and distributing questionnaires to 50 respondents, using the Binamarga method. Based on the results of road damage, the types of damage are longitudinal cracks, holes, corner breaks, surface texture damage, patches and height differences to the shoulder, with the priority order number obtained, namely number 2 from the UP range 0-7 then the value 2 is included in the category weight and must be included in the increase, while the results of the influence using the Likert scale method obtained a figure of 83.2% for road users and 84.0% for the community around the road and it is confirmed again by using the data on the effect of road damage on the community and road users using the SPSS application, the average value obtained from the questionnaire data is: 3.76 and falls into the category of Hight Interpretation with a standard deviation of 1.287 where the road must be repaired.